UJI TOKSISITAS DENGAN METODE BSLT PADA NANOPARTIKEL KOMBINASI OBAT CISPLATIN, BOVINE SERUM ALBUMIN DAN ASAM FOLAT - Ersalina Nidianti; Ary Andini (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Cancer is a non-communicable disease that causes morbidity and mortality in all regions of the world. Cancer treatment is important in reducing the high number of deaths (mortality) due to cancer sufferers. One of the cancer treatments is using chemotherapy drug cisplatin. However, cisplatin drug has side effects, namely nephrotoxicity, ototoxicity, neurotoxicity, hemotoxicity, cardiotoxicity, and hepatotoxicity. Therefore, the combination of cisplatin in albumin nanoparticles and modification of the bond using folic acid as an alternative solution minimizes the resulting toxic effects. This study aimed to determine the toxicity effect of the cisplatin drug formulation with a combination of bovine serum albumin (BSA) nanoparticles and folic acid through the Brine Shrimp Lethality Test (BSLT) method. The research methods used were BSA nanoparticle synthesis (NP-BSA), NP-BSA Synthesis with Cisplatin Drug (CP-NP-BSA), Folic Acid Synthesis with CP-NP-BSA Combination (As-CP-NP-BSA). Then, a toxicity test was carried out using the BSLT method to determine the toxicity level of BSA nanoparticles and the effect of adding folic acid in the cisplatin drug in the nanoparticles. The results showed that the absorbance of the 358 nm As-CP-NP-BSA UV-Vis spectrophotometer was 0.86. The toxicity level of the NP-BSA with the LC50 value was 69.23 ppm while the As-CP-NP-BSA LC50 toxicity level was 56.56 ppm. Nanoparticles consisting of a combination of bovine serum albumin, cisplatin and folic acid can be used as candidates for anticancer drugs